Landscape's Revenge The ecology of failure in Robert Walser and Bernardo Carvalho - Yurgel, Caio (Latin American Literatures in the World / Literaturas Latinoamericanas en el Mundo, 2018)
Drawing from diverse critical traditions from Latin-America and Europe, this work posits the landscape as the pathway to the hidden, dark depths of Robert Walser's and Bernardo Carvalho's literary projects. Behind the deceivingly idyllic or exotic sceneries lies a fictional stage riddled with irony and failure, with anti-heroes and outcasts who, with their dying breaths, narrate a world that is slowly undoing itself.